Los valores organizacionales y el desempeño laboral en los trabajadores del banco Interbank plaza Iquitos - año 2018 - Chong Vela, Rilke (2021)
The objective of this research was to determine the relationship between organizational values and job performance in workers at BANCO INTERBANK, Plaza Iquitos, period 2018. The research is descriptive, correlational, not experimental; the population was 34 workers and the sample was non-randomly and for convenience, and is formed of all the entire population because it is very small. The technique used was the survey and the instruments were two questionnaires elaborated with 36 questions, which allowed to identify six components in the organizational values: (1) sense of humor, (2) passion for the client, (3) innovation, (4) collaboration, (5) integrity and (6) courage and three components in job performance: (1) quality and productivity, (2) knowledge and (3) teamwork. The data processing was done with the help of the SPSS version 23 statistical program, which allowed the selection, storage and processing of the information obtained based on a data matrix. The statistical test used was the non-parametric Chi square test to determine the relationship between variables. Conclusion: There is a relationship between organizational values and job performance in the employees of BANCO INTERBANK Plaza Iquitos - 2018 period.